Entry and survival of Salmonella typhimurium in dendritic cells and presentation of recombinant antigens do not require macrophage-specific virulence factors - Niedergang, Florence (The National Academy of Sciences, 2000)
Macrophages have long been regarded as the main target encountered by Salmonella typhimurium, a Gram-negative facultative intracellular pathogen that invades the intestinal mucosa. S. typhimurium, however, are first internalized by dendritic cells. To gain new insights into the interactions between Salmonella and the dendritic cells, we compared the fate of wild-type S. typhimurium and the virulence-attenuated PhoP constitutive (PhoP(c)) strain. The PhoP(c) strain is impaired for entry and survival in mammalian cells and is poorly processed by macrophages for antigen presentation on MHC class II molecules. Here, we show that bone marrow-derived dendritic cells can similarly process and present a foreign antigen expressed by the invasive wild-type and the attenuated PhoP(c) S. typhimurium. This property correlates with equivalent entry and survival efficiencies of both strains in dendritic cells. In addition, Salmonella strains mutated in mgtCB, sseC, and orfL genes required for macrophage survival showed no defect in survival in dendritic cells. Together, these results indicate that uptake of Salmonella by dendritic cells and subsequent antigen processing and presentation do not depend on virulence factors important in macrophages.